Method of problem solving from Islamic thought perspective : a case study of Sisters in Islam / Zuraidah binti Senik @ Kamaruddin - Senik @ Kamaruddin, Zuraidah (2015)
ZURAIDAH BINTI SENIK @ KAMARUDDIN. Method of Problem Solving from Islamic Thought Perspective: a Case Study of Sisters In Islam. Thesis, Kuala Lumpur: University of Malaya, Kuala Lumpur, Malaysia, 2015. The objectives of the study are: to illustrate Sisters In Islam as a women’s organisation in struggling for women’s rights to achieve its objectives; to analyze the method of problem solving deployed by SIS; and to critically evaluate the method of problem solving used by SIS from an Islamic thought perspective. In this study, the methods adopted are library research (content analysis; data analysis; data gathering; and comparative analysis) and field work. Based on the study, it is found that SIS is an organisation registered as an NGO in 1993. The study identifies that the main objectives of SIS’s establishment according to this group are to promote a framework for the rights of women in Islam, abolish discrimination against them, enhance public consciousness and reform laws and policies within the framework of justice and equality in Islam. The group is also very active in promoting its objectives to achieve its aims. Through Amina Wadud, the group has engaged actively in a model of Qur’anic hermeneutics which they claimed concerned with the aspect of the text’s context in which it was revealed; the text’s grammatical composition; and the text’s worldview. Based on the study, it is found that the method of problem solving applied by SIS through the model of Qur’anic hermeneutics does not fulfil the requirements of the acceptable method of problem solving from an Islamic thought perspective. The analysis also shows that the method of problem solving through ijtihād as interpreted by SIS does not fulfil the proper methods of ijtihād within the Islamic context. Based on the analysis, it is also deduced that the group does not fully implement their method of problem solving in resolving matters relating to the issues of ṭalāq, taʻlīq, khulʻ and fasakh, but they seem to favour the opinions of sects other than al-Shāfiʻī as well as those that are not Jumhūr in most of their recommendations. Whereas in the issues relating to ʻawrah and enforcing public morality, it is found that SIS’ method of problem solving efforts in understanding these issues is mostly based on their opinions and rationale. Their method applied in the issues relating to ʻawrah and enforcing public morality does not fulfil the requirements for the acceptable method of problem solving from Islamic thought perspective. In the issues relating to enforcing public morality, SIS also appears to be partial to perspectives that come from the West in most of their opinions, especially in defining and understanding certain terminologies. Hence, the proposed solutions and ideas by SIS in the issues relating to ʻawrah and enforcing public morality do not coincide with the Qur’an and Sunnah. According to Islamic thought perspective, this situation happen because SIS do not apply the proper method of problem solving in giving the solutions to the issues relating to ʻawrah and enforcing public morality.